ADSORPTION OF METHYLENE BLUE USING SURFACE MODIFIED ACTIVATED CARBON - SAAFIE, NABILAH (2020)
Variousmodification methods were established to firm the application of commercial activated carbon (AC)especially in dye removal and to enhance its capacity. This method slightly changes the active carbon surface area thus created more active sites for desired contaminants. Dye removal through adsorption by modified AC occurs due to the formation of a surface complex between the dye ions and the surface functional groups of AC. Accordingly, the commercial AC with enhanced adsorption capacity performance is comprehensively investigated via modulating the carbon structural characteristics